Asuransi Dalam Perspektif Syariah - Damisa, Arti (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Takaful should be based on three principles: the principle of responsible, the principle of mutual help and work together, as well as the principle of protecting each other. Thus, al-ta'min or takaful seen from the perspective of mutual understanding muamalah sharia have to bear the risks against each other, so that one another guarantor and risk of loss. The third principle is basically his form of worship that is tabarru. Mutual bear the risk on the basis of helping each other in goodness with the way each cleanup tabarru or worship funds intended to cover these risks. Willingness